SOX17 expression and its down‐regulation by promoter methylation in cervical adenocarcinoma in situ and adenocarcinoma. Issue 3 (1st December 2019) - Hopman, Anton N H; Moshi, Jobran M; Hoogduin, Klaas J; Ummelen, Monique; Henfling, Mieke E R; van Engeland, Manon; Wouters, Kim A D; Stoop, Hans; Looijenga, Leendert H J; Ramaekers, Frans C S
Abstract : Aims: SOX17 expression has not been studied in glandular lesions of the uterine cervix like adenocarcinoma in situ (AIS) and invasive adenocarcinomas (AdC), whereas SOX17 promoter CpG island methylation has been reported. Therefore, the aim of this study was to relate the topographical distribution of SOX17 expression and SOX17 methylation status to each other, and to SOX2 expression, human papillomavirus (HPV) type, and physical status of the virus. Methods and results: Immunohistochemistry was used in 45 cases to assess expression of SOX17 and SOX2. SOX17 promoter methylation was determined in 25 cases by means of bisulphite conversion and methylation‐specific polymerase chain reaction. SOX17 and SOX2 showed a mutually exclusive expression pattern in normal epithelium, with a sharp delineation in the squamocolumnar junction. SOX17 was found in endocervical columnar and reserve cells, whereas SOX2 was exclusively found in squamous epithelium. In both glandular lesions and cases with coexisting glandular and squamous intraepithelial components, a complex combination of SOX17 and SOX2 expression patterns was seen and mutually exclusive expression was lost. Frequently, gain of expression of SOX2 was found and expression of SOX17 was lost. Methylation of the CpG island in the SOX17 promoter was shown to be strongly associated with loss of expression of SOX17 ( P = 0.0016). Conclusions: In this study, we show for the first time a direct correlation between the topographical distribution of SOX17 expression and the methylation status of its gene promoter. This explains the heterogeneity of SOX17 expression in the glandular lesions of the cervix. No correlation was found between HPV type and physical status of the virus on the one hand and methylation status on the other.